Editorial Board - -, - (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology; Vol 1 No 2 (2023): The Flow of Things and Bodies: The Production of Flowers in La Trinidad, Benguet, 2025)
-